Forming a General Cultural Outlook for Future Foreign Language Teachers - Dilbar, Sadullayeva (Indonesian Journal Publisher, 2024)
In this article, information about the formation of a general cultural outlook of teachers, the changes that the teacher should implement in his students, the criteria for the formation of the world-view, the main components of various models of general pedagogical knowledge, the pedagogical and psychological components of the teacher's culture, the methodology of the formation of the spiritual and moral culture of students is highlighted. The development of a universal worldview in students is a complex, non-hereditary process that has been largely overlooked in educational systems, leading to challenges in higher education. Cultivating this perspective is crucial for future educators, as it enhances their professional and personal development, helping them overcome apathy and indifference. Therefore, higher education must prioritize fostering a universal outlook to adequately prepare future teachers for a globalized society.